Industrial training report: Universiti Malaysia Kelantan / Muhammad Azmawi Barhanudin - Barhanudin, Muhammad Azmawi (Perpustakaan Tengku Anis, 2016)
Based on the period from 01 August to 31 December 2016 in Department Information System and Multi Camera Production at University Malaysia Kelantan. The industrial training has been conducted in the process of gaining knowledge and information with working environment instead of just learning the theory only. It is the requirements of subject IMC 690 (Industrial Training) for students of Bachelor of Science (HONS), Information System Management which requires students to choose local libraries to do the industrial training. The office of Library and Knowledge Management, Universiti Malaysia Kelantan (UMK) has been chosen as a place to do this industrial training for about five months. Trough the industrial training, students will learn in details about the flow steps for any process done in the library especially at department of information system and multi camera production (MCP) and also will adapted the skills and ethics of work like a professional officer. Students will involved in each department available in the chosen library. This industrial training is suitable for students in preparation to be professional worker in the future.